Does the plasticity of neural stem cells and neurogenesis make them biosensors of disease and damage? - Rodríguez-Bodero, Ane; Encinas-Pérez, Juan Manuel (Frontiers in Neuroscience, 2022)
Postnatal and adult neurogenesis takes place in the dentate gyrus of the hippocampus in the vast majority of mammals due to the persistence of a population of neural stem cells (NSCs) that also generate astrocytes and more NSCs. These are highly plastic and dynamic phenomena that undergo continuous modifications in response to the changes brain homeostasis. The properties of NSCs as well as the process of neurogenesis and gliogenesis, are reshaped divergently by changes in neuronal activity and by different types of disease and damage. This richness of plastic responses identifies NSCs and newborn neurons as biosensors of the health state of the hippocampus, detecting and providing useful information about processes such as neuronal and network hyperexcitation, excitotoxicity, neurodegeneration, and neuroinflammation. Learning to gather and use this information is a challenge worth of our attention.